Faktor-Faktor yang Mempengaruhi Nilai Perusahaan Sub Sektor Telekomunikasi Periode 2011-2021 - Jefanya Jane Odella; Neneng Miskiyah; Esya Alhadi (Politeknik Negeri Sriwijaya, 2024)
This research aims to analyze the effect of Return on Assets and Debt to Equity ratio on firm value in telecommunications sub-sector companies on the Indonesia Stock Exchange. The research data uses secondary data, data collection techniques through library research and documentation from the official IDX website. The research sample consisted of 18 companies that met the specified criteria. This study uses multiple regression analysis to evaluate the effect of Return on Assets and Debt to Equity ratio variables on firm value. The results of this research show that Return on Assets and Debt to Equity ratio significantly affect firm value.